2013
DOI: 10.4028/www.scientific.net/amr.824.283
|View full text |Cite
|
Sign up to set email alerts
|

Thin-Layer Drying of Pumpkin Fruit Slices

Abstract: Pumpkin(Cucuribita Spp.)fruit slices were subjected to pre-drying treatments and drying using methods of uncontrolled sun and oven drying. The two-way interaction between drying methods and pre-drying treatments had significant effect on chemical qualities. Pumpkin subjected to salt solution dipping treatment and oven dried had higher chemical concentrations. Among the pumpkin fruit accessions, pumpkin accession 8007 had the superior TSS after drying. Among the three pre-drying treatments, salt solution dippin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
2
0
0
Order By: Relevance
“…Drying the samples at highest temperature (zone III) also leads to fast drying and a decrease in conversion of starch into weak acid and as a result decreases in acid production. The decrease in pH for citric acid-treated pumpkin powder is in good agreement with Fana et al [52], who work on orange fleshed sweet potato flour in which citric acidtreated flour shows low pH or high acidity value. This study confirmed that concentration of titratable acidity increases as drying time increases and air temperature decreases.…”
Section: Ph and Titratable Acidity (Ta)supporting
confidence: 89%
See 1 more Smart Citation
“…Drying the samples at highest temperature (zone III) also leads to fast drying and a decrease in conversion of starch into weak acid and as a result decreases in acid production. The decrease in pH for citric acid-treated pumpkin powder is in good agreement with Fana et al [52], who work on orange fleshed sweet potato flour in which citric acidtreated flour shows low pH or high acidity value. This study confirmed that concentration of titratable acidity increases as drying time increases and air temperature decreases.…”
Section: Ph and Titratable Acidity (Ta)supporting
confidence: 89%
“…This is related to the fact that one of the functions of salt pretreatment is to improve the TSS of the dried product by preventing the desolation of soluble components. This study followed the result of Teferi et al [52], who observed the maximum TSS for salt treated and minimum for different untreated accessions of pumpkin powder. The pumpkin powder treated with salt (2%) and citric acid generally showed relatively higher TSS.…”
Section: 24supporting
confidence: 79%